Discovery of novel melatonin–mydroxyquinoline hybrids as multitarget strategies for Alzheimer’s disease therapy - Wang, Wei; Pan, Tingting; Su, Rui; Chen, Mingbin; Xiong, Wandi; Xu, Congjun; Huang, Ling (Frontiers in Chemistry, 2024)
Alzheimer’s disease (AD) is a neurodegenerative disease that seriously affects human health, and current treatment strategies are far from meeting clinical needs. Inspired by multi-target drug design strategies, a series of novel natural products-based melatonin–hydroxyquinoline hybrids were designed and synthesized, targeting anti-oxidation and metal-chelating at the same time. Most of the compounds showed significant oxygen radical absorbance capacity and Aβ1–42 aggregation inhibition. Moreover, the compounds possess good blood-brain barrier permeability. 6b and 6c have a good ability to alleviate oxidative stress induced by hydrogen peroxide. 6b and 6c possess metal-chelating properties with the chelation ratio being 2:1. Furthermore, 6b can significantly mitigate metal-induced Aβ aggregation. This work may provide a new multi-target treatment strategy for Alzheimer’s disease.